Littoral free living nematode fauna of Socorro Island, Colima, Mexico - De Jesús-Navarrete, Alberto (HIDROBIOLÓGICA, 2017)
In order to study the littoral nematode fauna in the Mexican Pacific, sediment samples were collected in three sites at Socorro Island, during November 1997. A total of 30 species of nematodes, from three orders and 15 families were determined. Order Chromadorida had 20 species, with Metachromadora (Chromadoropsis) sp. and Rhips sp. as the most abundant genus (19 and 17 ind./0.008 m2 , respectively). Monhysterida had six species and Enoplida four species, being Enoplolaimus sp. the most abundant genera with 14 ind./0.008 m2 . Higher number of species was found at Bahia Blanca (24). Six species are considered cosmopolitan; two tropical and 21 are undescribed. All species are first records for the Mexican Pacific Ocean.